Can law offer certainty and security in today’s world? An outline of a response based on the value of legal certainty - Sánchez Barroso, Borja (Razón y fe, 2019)
The ability of law to provide certainty and security in an increasingly unstable and complex world depends to a large extent on the importance attached to legal certainty. This value is threatened in the current context, given the emergence of a new principle: the imperative of flexibility. Recovering the value of legal certainty, despite the difficulties that this entails, may be the only way to preserve the very nature and function of law.
Keywords: legal certainty; certainty; predictability; judiciary; legal principles; flexibility